Effect of 7E Learning Cycle on Cell Concept Performance Among Senior Secondary School Slow Learners in Katsina Metropolis, Nigeria - Ibrahim, Ahmed; Lakpini, M.A.; Abdulkarim, B.; Falalu, M.K. (Kashere Journal of Education, 2022)
The study investigated effect of 7E Learning Cycle on Cell Concept Performance among Senior Secondary School Slow Learners in Katsina Metropolis, Nigeria. Solomon four group design was used. One of the experimental and control groups were pre-tested and post-tested while the second groups were post-tested only. Four schools were selected using simple random technique and assigned to experimental and control groups. The total population was 5,459 SSII Biology students in Katsina Metropolis, out of which 352 students were purposively sampled using Student Intelligence Quotient Ability Test (SIQAT) and retrospective performance. Cell Performance Test (CPT) was used for data collection. The data was analysed using mean, standard deviation, and independent t-test, the post test result revealed significant difference between slow learners exposed to 7E learning cycle in the experimental group and those exposed to conventional method, 7E group performed significantly better than those in the control group. It was concluded that 7E learning cycle enhance better understanding of cell concepts. Some of the recommendations include; teaching of biology should be conducted using the 7E learning cycle as it makes students learn meaningfully and enhances better performance.